Teaching German - Kosimova M. N. (Scientific Trends, 2024)
Germans also work with children outside of school hours, so students communicate in German throughout their stay in the camp. The ultimate goal of mastering a foreign language is clear and simple – the ability to express oneself in a foreign language, that is, the development of that communicative and intercultural competence that allows one to work with information in the target language, both orally and in writing according to the subject of the situation.
Keywords: Language, qualities, section, problems, teaching aids, oral, motivation.